1999
DOI: 10.1136/mp.52.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cadherin and catenin expression during the biological progression of melanocytic tumours

Abstract: Aims-Compelling evidence from cell culture studies implicates cadherins in the neoplastic progression of melanocytic tumours but few reports describe the expression of cadherins and the related transmembrane proteins, catenins, in a full range of benign and malignant excised melanocytic tumours. Methods-Using immunohistochemistry and western blotting after tissue fractionation, the pattern of expression of cadherins/ catenins was studied in a range of surgically excised melanocytic tumours, from dysplastic nae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
92
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 27 publications
12
92
1
2
Order By: Relevance
“…In accordance with data published by Sanders et al (24), we have shown that P-cadherin and h-catenin have extremely similar expression profiles through Spearman correlation coefficients and a dendrogram after hierarchical clustering. According to our data, p120-catenin and a-catenin also share similarity to the former proteins.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In accordance with data published by Sanders et al (24), we have shown that P-cadherin and h-catenin have extremely similar expression profiles through Spearman correlation coefficients and a dendrogram after hierarchical clustering. According to our data, p120-catenin and a-catenin also share similarity to the former proteins.…”
Section: Discussionsupporting
confidence: 76%
“…This same study reported no association between either p120-catenin or g-catenin with both Breslow thickness and tumor status (23). One other study attempted to investigate g-catenin but could not detect this marker in their immunohistochemical assay (24).…”
Section: Introductionmentioning
confidence: 96%
“…Immunohistochemical studies of E-cadherin expression in malignant melanomas demonstrated significant down-regulation of E-cadherin in the tumor tissue compared with benign melanocytes and melanocytic nevi (4,5). Evidence for the functional relevance of this phenomenon was obtained by Herlyn and co-workers (19 -21), who showed that down-regulation of E-cadherin leads to deregulated control of melanocyte proliferation by keratinocytes and in parallel to an invasive growth behavior.…”
mentioning
confidence: 84%
“…Owing to its critical function in intercellular adhesion, E-cadherin has also been assumed to act as a tumor suppressor negatively regulating several critical steps of invasion and metastasis. Loss of E-cadherin expression during tumor development was recently observed in a variety of different tumor types including malignant melanomas (Berx et al, 1995(Berx et al, , 1996Tamura et al, 1996a, b;Silye et al, 1998;Sanders et al, 1999;Melki et al, 2000;Poser et al, 2001). Further, we have shown that inhibition of the expression of the transcriptional repressor snail induced re-expression of Ecadherin in Mel Im melanoma cells (Poser et al, 2001).…”
Section: Introductionmentioning
confidence: 99%